Symmetry and phase transitions in (AsO4) 2H2 (U02) 2. 8 H20. - Rodríguez de Benyacar, M. A.; Lanza de Dussel, H. (Taylor & Francis, 1978)
Fil: Rodríguez de Benyacar, M. A. Comisión Nacional de Energía Atómica; Argentina